Effect of Garlic Infusion on Growth Performance, Carcass Traits, and Meat Quality of Ducks - Novi Akhirini; Agung Irawan; Wara Pratitis Sabar Suprayogi; Muhammad Arif Darmawan; Wahyu Subagio Saputro; Pramita Nindya Saraswati; Wahyu Setyono; Min Gao; Aan Andri Yano (Jurnal Peternakan Integratif, 2026)
The use of antibiotic growth promoters (AGPs) has been increasingly restricted due to concerns regarding antimicrobial resistance and food safety. Consequently, natural feed additives have gained significant attention as sustainable alternatives in poultry production systems. This study aimed to evaluate the effects of garlic (Allium sativum) infusion on growth performance, carcass characteristics, and meat quality of Tegal ducks. A total of 120-day-old ducks were randomly assigned to four treatments in a completely randomized design with six replicates per treatment. The treatments consisted of a basal diet (control) and basal diet supplemented with garlic infusion at levels of 3%, 6%, and 9%. The experiment was conducted for 8 weeks. The results showed that garlic infusion significantly improved (P < 0.01) live weight, carcass weight, and carcass percentage. The highest values were observed in ducks supplemented with 9% garlic infusion. However, no significant effect (P > 0.05) was found on non-carcass weight and percentage. In terms of meat quality, garlic infusion significantly reduced fat content (P < 0.05), while collagen, protein, and moisture contents were not affected (P > 0.05). The reduction in fat content is associated with the bioactive compounds in garlic, particularly allicin, which plays a role in inhibiting lipid biosynthesis and improving metabolic efficiency. In conclusion, garlic infusion can be used as a natural feed additive to improve growth performance, carcass yield, and meat quality of ducks by reducing fat content without negatively affecting other physicochemical properties. This study highlights the potential of garlic infusion as a sustainable alternative to antibiotic growth promoters in poultry production